Performance analysis of priority queuing packets scheduling / Mohd Husni Din - Din, Mohd Husni (2009)
The primary purpose of this thesis is to study the performance of the Priority Queuing (PQ) packet scheduling. The project starts by providing the theoretical foundations that help understand the topics that are handled in this thesis. Then the implementation of a network scenario was done in OPNET Modeler 10.5 which is a network simulator that offers the tools for model design, simulation, data mining and analysis. The simulation of this network will be run for two different conditions and the example of packet delivery for three applications will be used in these projects, which are FTP, Video Conferencing and Voice over IP (VoIP). After'obtaining the results, we will produce an analysis that shows the performance of PQ for both queues.